PENGARUH KONTRIBUSI PENERIMAAN RESTRIBUSI PASAR TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN ACEH BARAT DAYA. - Muzakir Muzakir; Cici Damayanti (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2021)
Abstract One of the benchmarks to see the ability of regions in implementing regional autonomy is to measure how much the financial capacity of a region to carry out regional autonomy in accordance with law number 23 of 2014 concerning regional government, one of which comes from regional revenue. The level of effectiveness of receiving market fees in Aceh Barat Daya District is still quite effective, with an average level of effectiveness of 63.46. This indicates that market fees have not played an optimal role in increasing local revenue in Aceh Barat Daya District. The contribution of the market retribution to Regional Original Income (PAD) in Aceh Barat Daya District is still very low, namely an average of 0.35 percent per year. the contribution of levies to local revenue continues to decline every year starting from 75.06 down to 0.21 percent in 2017